Toward an historically informed Asian model of public Relations - Halff, Gregor (Institutional Knowledge at Singapore Management University, 2014)
This paper undertakes a meta-analysis of the 51 historiographies of public relations in Asia-Pacific countries to identify common themes, threads and theoretical insights. The authors propose a set of necessary components for the study of Asia-Pacific public relations drawn from a historical perspective that differs from the paradigmatic underpinnings of the major Western models. They draw conclusions about epistemological and practice differences between public relations in the West and in the Asia-Pacific region in a globalizing world.